PENGARUH JARAK TANAM JAGUNG MANIS (Zea mays Saccharata STURT) DAN VARIETAS KUBIS (Brassica oleracea VAR. CAPITATA) TERHADAP HASIL JAGUNG MANIS DAN KUBIS PADA SISTEM TUMPANGSARI DI DESA CANDI KUNING, TABANAN - I Wayan Sunarta (AGRICA, 2009)
Diversification of plant species is needed to anticipate price fluctuation of vegetables. Intercropping system compared to monoculture can give more benefits to farmers. The arrangement of plant spacings of sweet corn and cabbage variety is expected to result in higher yields and benefits in intercropping. The field experiment, which had the objective to study the effects of plant spacing of sweet corn and cabbage variety on yields of sweet corn and cabbage in the intercropping system, had been conducted from March to July 2008. The experiment was carried out at the dryland farming area at Candikuning Village, district of Baturiti, Tabanan regency, 1.200 m asl. In the experiment, a randomized complete block design with two factors namely plant spacing of sweet corn (120 cm x40 cm, 180 cm x 40 cm and 240 cm x 40 cm) and variety of cabbage (Green Nova and Summer-Autumn) were used. Plant spacing of cabbage was 60 cm x 40 cm. All treatments were replicated four times. The results of the experiment showed that the effect of interaction between plant spacing of sweet corn and cabbage variety in intercropping was not significant on yields of sweet corn and cabbage. Individually, sweet corn plant spacing of 120 cm x40 cm gave the highest fresh weight of cob without husk (10,91 t ha"'), which was 44.50% and 80.93% respectively higher than the spacing of ! 80 cm x 40 cm and 240 cm x 40 cm. The spacing of 180 cm x 40 cm resulted in not the significantly different fresh weight of cob with husk but gave the highest fresh weight of cabbage heads (56.101 ha'1), which was 27.36% higher than that at sweet corn spacing of 120 cm x 40 cm and was not significantly different from that at 240 cm x 40 cm. Cabbage variety Green Nova gave the highest head (56.101 ha1), which was 14.48% higher than variety Summer-Autumn. Intercropping between cabbage variety Green Nova and Sweet corn at 180 cm x 40 cm spacing resulted in the highest benefit (Rp. 20,488125 t ha'1), which was Rp. 3,335500 higher than the average benefit of cabbage monoculture. The efficiency of land use in intercropping was higher (LER: 1.69) than in monoculture (LER: 1). It is suggested to use cabbage variety Green Nova intercropped with sweet corn at I 80 cm x 40 cm spacing. An experiment studying the effect of cabbage intercropped with sweet corn and other short season vegetables planted after harvesting cabbages is also suggested.